Modeling of Precast Reinforced Concrete Beam-column Joints Under Cyclic Loading. Issue 14 (26th October 2022) - Tarabia, Ahmed M.; Etman, Emad E.; Allam, Said M.; Aboelhassan, Mohamed G.
ABSTRACT: This paper aims to present a numerical nonlinear spring model able to simulate the cyclic behavior of the monolithic and the precast bolted reinforced concrete beam-column connections with the consideration of the concrete interface friction and the dowel action of reinforcing steel bars. The accuracy of this proposed model was verified by the comparison with some existing experimental test results. Generally, these comparisons showed good agreement and the model could simulate the cyclic performance of the tested specimens. Also, a study of the effect of increasing the area of shear reinforcement at the shear key zone was performed and discussed.